Cytomegalovirus duodenitis associated with life-threatening duodenal hemorrhage in an immunocompetent patient: A case report. (2017) - Shen, Lucy; Youssef, David; Abu-Abed, Suzan; Malhotra, Sangita K.; Atkinson, Kenneth; Vikis, Elena; Melich, George; MacKenzie, Shawn
Highlights: Gastrointestinal cytomegalovirus infections can occur in immunocompetent patients. Diagnosis relies on histopathologic examination of endoscopic biopsy specimen. Early recognition and antiviral treatment are important to patient outcome. Cytomegalovirus duodenitis has significant potential to be life-threatening. Abstract: Introduction: Cytomegalovirus (CMV) is known to be opportunistic in immunocompromised patients. However, there have been emerging cases of severe CMV infections found in immunocompetent patients. Gastrointestinal (GI) CMV disease is the most common manifestation affecting immunocompetent patients, with duodenal involvement being exceedingly rare. Presented is a case of an immunocompetent patient with life-threatening bleeding caused by CMV duodenitis, requiring surgical intervention. Presentation of case: A 60-year-old male with history of disseminated Methicillin-sensitive Staphylococcus aureus (MSSA) bacteremia and aortic valve infective endocarditis, presented with life-threatening upper GI hemorrhage. Endoscopy revealed ulcerations, with associated generalized mucosal bleeding in the duodenum. After repeated endoscopic therapies and failed interventional-radiology arterial embolization, the patient required a duodenectomy and associated total pancreatectomy, to control the duodenal hemorrhage. Pathologic review of the surgical specimen demonstrated CMV duodenitis. Systemic ganciclovir was utilized postoperatively. Discussion: GI CMV infections should be on the differential diagnosis of immunocompetent patients presenting with uncontrollable GI bleeding, especially in critically ill patients due to transiently suppressed immunity. Endoscopic and histopathological examinations are often required for diagnosis. Ganciclovir is first-line treatment. Surgical intervention may be considered if there is recurrent bleeding and CMV duodenitis is suspected because of high potential for bleeding-associated mortality. Conclusion: Presented is a rare case of life-threatening GI hemorrhage caused by CMV duodenitis in an immunocompetent patient. The patient failed endoscopic and interventional-radiology treatment options, and ultimately stabilized after surgical intervention.